(untitled) (European Journal of Pure and Applied Mathematics, 2018)
The main aim of this paper is to introduce the notion of a partial transformation UP-algebra P(X) induced by a UP-algebra X and prove that the set of all full transformations T(X) is a UP-ideal of P(X).